2021
DOI: 10.1016/j.amjoto.2021.103065
|View full text |Cite
|
Sign up to set email alerts
|

Eight-month follow-up of olfactory and gustatory dysfunctions in recovered COVID-19 patients

Abstract: Purpose To investigate the recovery of loss of smell and taste among recovered COVID-19 patients. Materials and methods This cross-sectional follow-up study is a sequel to a study by Biadsee et al. Among the previous study population of 128 non-hospitalized patients, positive for COVID-19 by reverse transcription-polymerase chain reaction (RT-PCR), 97 patients participated in a survey designed for this study. Information and data regarding loss of smell and taste, rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 19 publications
4
51
0
Order By: Relevance
“…The remaining 18 studies were conducted in other regions (a pie chart showing distribution is included in the supplementary data provided— S1 Fig ). 10 studies were conducted in Asia: Turkey (n = 5) [ 18 , 27 , 38 , 41 , 50 ], Iran (n = 2) [ 22 , 55 ], India (n = 2) [ 33 , 52 ], Israel (n = 1) [ 32 ]. Four studies were conducted in North America: United States (n = 4), [ 21 , 42 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 18 studies were conducted in other regions (a pie chart showing distribution is included in the supplementary data provided— S1 Fig ). 10 studies were conducted in Asia: Turkey (n = 5) [ 18 , 27 , 38 , 41 , 50 ], Iran (n = 2) [ 22 , 55 ], India (n = 2) [ 33 , 52 ], Israel (n = 1) [ 32 ]. Four studies were conducted in North America: United States (n = 4), [ 21 , 42 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in Africa: Egypt (n = 2) [ 34 , 49 ], and two in South America: Brazil (n = 1) [ 53 ], Chile (n = 1) [ 15 , 53 ]. Of the 44 studies, twenty-five (56.8%) reported no funding requirements for the project [ 16 , 18 , 19 , 22 , 27 30 , 32 , 33 , 39 , 40 , 42 47 , 49 51 , 53 , 58 ]; six (13.6%) studies reported funding for the project (sources included academic institutions, government and not-for-profit organizations) [ 15 , 24 , 25 , 31 , 48 , 57 ], and thirteen (29.5%) did not report whether funding was provided [ 17 , 21 , 23 , 26 , 37 , 38 , 52 , 54 56 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, self-reported loss of smell and taste has been observed to be more prognostic than other symptoms including fatigue, fever, or cough in predicting symptomatic infection (Agyeman et al, 2020;Mastrangelo et al, 2021). Significantly, loss of taste is consistently reported as a common symptom of long COVID-19, defined as persistence of symptoms four weeks after infection (Biadsee et al, 2021). Following over four-hundred SARS-CoV-2 infected individuals for severity, improvement, and recovery of subjective chemosensory dysfunction for four months, Schwab et al have reported that the recovery from loss of taste became stagnant after about two months with little improvement subsequently (Schwab et al, 2021).…”
mentioning
confidence: 99%
“…2 weeks [ 67 , 68 ] and a minority of patients experiencing OD at 7-month follow-up [ 69 ]. Of interest are the minority of patients whose symptoms persist after several weeks [ 70 , 71 ]. For example, Riestra-Ayora and colleagues noted persistence of OD in 11.2% (14/125) patients at 6-month follow-up [ 72 ] and Nguyen and colleagues noted 24.0% (30/125) 7 months after onset [ 69 ].…”
Section: Main Textmentioning
confidence: 99%